MITRIS - high information technologies - Белецкий, А. Я.; Зубарев, В. В.; Нарытник, Т. Н.; Шевченко, P. A. (Proceedings of National Aviation University (archive), 2000)
Considered are characteristics structure and potentialities of microwave integrated teleradio information system